Merci Suarez Can't Dance - Book 2 - Medina, Meg (Somerville, Massachusetts : Candlewick Press, 2021)
Merci embarks on a seventh grade year shaped by high teacher expectations, a crush on a school-store co-worker, and a bossy classmate's plan for the annual Heart Ball.
Keywords: Cuban Americans -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Infatuation -- Fiction; Balls (Parties) -- Fiction; Grandparent and child -- Fiction; JUVENILE FICTION -- Family; JUVENILE FICTION -- Social Themes; JUVENILE FICTION -- Social Themes; Girls; Balls (Parties); Cuban Americans; Grandparent and child; Infatuation; Middle schools; Schools; Balls (Parties) -- Fiction; Girls -- Fiction; Love -- Fiction; School stories; Florida -- Fiction; Florida; School fiction; Novels; School fiction; Novels; Fiction; Juvenile works